Novel PbSe nanocrystals doped fluorogermanate glass matrix. (June 2015) - El-Rabaie, S.; Taha, T.A.; Higazy, A.A.
Abstract: PbSe nanocrystals doped fluorogermanate glass has been prepared via thermal treatment method. The nanocrystals were characterized by optical absorption, X-ray diffraction (XRD) and transmission electron microscope (TEM) analysis. PbSe nanoparticles of average radii 4.3, 5.9, 7.0 and 7.8 nm with cubic and orthorhombic crystal structure were formed in the fluorogermanate glass matrix. Also, the effect of annealing temperature on the nanocrystal sizes was studied. The obtained optical energy gap, E opt values show a decrease from 3.4 to 2.9 eV with increasing PbSe nanocrystal size. Raman spectroscopy confirmed the formation of PbSe nanoparticles by the appearance of surface and longitudinal optical phonons of PbSe.